Project Based Learning Model: Can It Improve Dribbling Skills In Soccer Games? - Hardinata, Riyan; Yosika, Ghana Firsta; Haïdara, Youssouf; Perdana, Rahmat Putra; Gustian, Uray; Suryadi, Didi; Sacko, Makan; Abidin, Muhamad Zainal (Indonesian Journal of Physical Education and Sport Science (Online), 2023)
Study purpose. The ability to dribble is a very important skill in soccer, because dribbling skills in soccer aim to be able to pass opponents so that players have the opportunity to provide bait. However, there are still many students who have difficulty in dribbling in soccer games. Materials and methods. This research uses a descriptive method in the form of Classroom Action Research. In this study using a learning tool, namely the Learning Implementation Plan (RPP). The data collection instrument is a test using periodical notes. The subjects in this study were all class XI students of State Senior High School 1, Merau District, Ketapang Regency, totaling 39 students Results. The results showed that there was an increase in cycle I of 25,6%, but this figure was still relatively low, so it was necessary to continue in cycle II. Based on the results in cycle II, it showed that 89.7% of students completed, and there was a difference in the increase in cycle I and cycle II, namely 64.1%. Based on these results, there is an increase in learning outcomes to dribble (soccer) through problem based learning models. Conclusion. The results of this study indicate that the problem based learning model can actually improve the learning outcomes of herding in soccer games. These results can be used as a reference in PJOK learning, especially in big ball game material (soccer).